Pengaruh Kepemimpinan Kepala Sekolah dan Kompetensi Guru terhadap Kinerja Guru Bidang produktif Jurusan Manajemen Bisnis di SMK Kota Jambi - Pratiwi Indah Sari; Yunia Wardi (Program Magister Pendidikan Ekonomi (S2), 2014)
The purpose of this study was to determine the effect of the principal leadership and the teacher competence consisting of pedagogic competence, personal competence, social competence, and professional competence on the performance of teachers in SMK City of Jambi. The population in this study was the teacher of existing productive fields in the SMK City of Jambi totaling 136 people. By using proportional random sampling technique analysis, the obtained of samples with the number of teachers is 94. The method of analysis used is path analysis, where the data acquisition is done through questionnaires, interviews, and literature as a reference for this study. The results showed that the influences of positive and significant the principal leadership and the teacher competence on performance of teachers in the productive field of SMK City of Jambi. Keyword : Principal Leadership, Teacher Competence, Performance of Teacher.